The decline of the labor share: New empirical evidence - Drago Bergholt; Francesco Furlanetto; Nicolò Maffei Faccioli (Norges Bank, 2019)
We estimate a structural vector autoregressive model in order to quantify four main explanations for the decline of the US labor income share: (i) rising market power of firms, (ii) falling market power of workers, (iii) higher investmentspecific technology growth, and (iv) the widespread emergence of automation or robotization in production processes. Identification is achieved with theory robust sign restrictions imposed at medium-run horizons. The restrictions are derived from a stylized macroeconomic model of structural change. Across specifications we find that automation is the main driver of the long-run labor share. Firms' rising markups can, however, account for a significant part of the accelerating labor share decline observed in the last 20 years. Our results also point to complementarity between labor and capital, thus ruling out capital deepening as a major force behind declining labor shares. If anything, investment-specific technology growth has contributed to higher labor income shares in our sample.
hdl:11250/2652986
Keywords: E2; D2; D4; J3; L1; 330; Labor income share; secular trends; technological progress; market power